Does patient’s sex influence treatment in primary care? Experiences and expressed knowledge among physicians – a qualitative study - Loikas, Desirée (BMC Fam Pract, 2015)
BACKGROUND: Biological and sociocultural differences between men and women may play an important role in medical treatment. Little is known about the awareness of these differences among general practitioners (GPs) and if they consider such differences in their medical practice. The aim of this study was to explore GPs’ perception of sex and gender aspects in medical treatment. METHODS: We conducted five focus group discussions (FGDs) with 29 physicians (mainly GPs) in Sweden. A discussion guide with semi-structured questions was used. All FGDs were audio-recorded and transcribed word-by-word. Data were analysed through inductive thematic analysis with no predetermined categories. RESULTS: Three main categories emerged from the data. The first category emphasised GPs’ experiences of sex and gender differences in diagnosing and assessment of clinical findings. Medical treatment in men and women was central in the second category. The third category emphasised GPs’ knowledge of sex differences in drug therapy. CONCLUSIONS: The GPs stated they had little knowledge of sex and gender differences in drug treatment, but gave multiple examples of how the patient’s sex affects the choice of treatment. Sex and gender aspects were considered in diagnosing and in the treatment decision. However, once the decision to treat was made the choice of drug followed recommendations by local Drug and Therapeutics Committee, which were perceived to be evidence-based. In the analysis we found a gap between perceived and expressed knowledge of sex and gender differences in drug treatment indicating a need of education about this to be included in the curriculum in medical school and in basic and specialist training for physicians. Education could also be a tool to avoid stereotypical thinking about male and female patients.